English Teachers’ Decision in Utilizing Textbook in Their Classroom - Imelda Mallipa; Riana Murianty (Linguistic, English Education and Art (LEEA) Journal, 2019)
This study was conducted at SMAN 1 Manokwari, West Papua. The data were collected through classroom observation and interview with two qualified English teachers in the school. The results showed that the English textbooks provided were the main learning source in teaching reading comprehension. The teachers contextually modified the sequence of the tasks and lessons from the textbooks before assigning them to the students in teaching speaking, listening and grammar. Some factors that were considered by the teachers in selecting materials were the availability of learning materials in school, students’ needs, and students’ level of English competence, school facilities and the national exam. The results of these study consider practical implications to give teachers, practioners, other reserachers and author of textbooks in developing teaching materials to be used in different context of classroom. Keywords: the 2013 curriculum, decision making, textbook use